2020
DOI: 10.3389/fmicb.2020.00994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alfalfa Hay and Starter Feeding Intervention on Gastrointestinal Microbial Community, Growth and Immune Performance of Yak Calves

Abstract: The present study aims to evaluate the effects of different early weaning paradigms, which supplied with extra alfalfa hay, or starter feeding, or both alfalfa hay and starter feeding, along with the milk replacer, on the gastrointestinal microbial community, growth, and immune performance of yak calves. Twenty 30-day-old male yak calves were randomly assigned to four groups, including the control (CON), alfalfa hay (A), starter feeding (S), and starter plus alfalfa hay (SA) groups. The gastrointestinal microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 76 publications
5
20
0
Order By: Relevance
“…The current study showed that the phyla Bacteroidetes and Firmicutes were the dominant bacteria of GIT in GRYs and GNYs. Consistent with our study, the two phyla were also found to be presented abundantly in the GIT of dairy cattle (Mao et al, 2015), goats (Li et al, 2019), yaks (Cui et al, 2020b), and steers (de Oliveira et al, 2013), suggesting the functional importance of Bacteroidetes and Firmicutes in the GIT of ruminants. In addition, the PCoA results revealed that the bacterial composition and structure in each segment of GIT were distinct between the GNY and GRY groups.…”
Section: Discussionsupporting
confidence: 90%
“…The current study showed that the phyla Bacteroidetes and Firmicutes were the dominant bacteria of GIT in GRYs and GNYs. Consistent with our study, the two phyla were also found to be presented abundantly in the GIT of dairy cattle (Mao et al, 2015), goats (Li et al, 2019), yaks (Cui et al, 2020b), and steers (de Oliveira et al, 2013), suggesting the functional importance of Bacteroidetes and Firmicutes in the GIT of ruminants. In addition, the PCoA results revealed that the bacterial composition and structure in each segment of GIT were distinct between the GNY and GRY groups.…”
Section: Discussionsupporting
confidence: 90%
“…Our study found that the phyla Firmicutes and Bacteroidetes were the dominant bacteria of rumen and feces in YAK and CAY groups. Consistent with our results, the 2 phyla were also identified to be presented abundantly in the gut of yaks (Xue et al 2016 ; Cui et al 2020 ), dairy cattle (Mao et al 2015 ) and steers (Oliveira et al 2013 ), suggesting the important functional role of Bacteroidetes and Firmicutes in the gut of ruminants. Furthermore, the PCoA results revealed that the bacterial composition and structure in the rumen were distinct between YAK and CAY groups.…”
Section: Discussionsupporting
confidence: 89%
“…The investigation in jejunum could help better understand the immune responses in neonatal cattle fed a highly fermentable diet [ 71 , 72 ]. Our work indicated that the expression of immunity-related genes in the jejunum was highly responsive to ruminal acidosis.…”
Section: Discussionmentioning
confidence: 99%